A Quasi-experimental Research Endeavor to Evaluatethe Impact of a Structured Instructional Program on Adults' Comprehension of Disaster Awareness and Management in Chosen Villages Situated in Moga,Punjab - Ravinder Kaur; Arshdeep Kaur; Sukhdeep Kaur (International Journal of Biomedical Innovations and Engineering, 2023)
A quasi-experimental research was conducted to evaluate the efficiency of a structured instructional program on adults' comprehension of disasters and their management. The study involved a sample of 60 adults, divided equally into an experimental group of 30 and a control group of 30. The knowledge score of adults in experimental group regarding disaster and its management among adults was average (54%) and below average (46%) before imparting the structured teaching programme and knowledge score of adults was good (70%) and average (30%) after imparting structured teaching programme. The experimental group exhibited a noteworthy increase in mean post-test knowledge score (21.7), Surpassing the mean pre-test knowledge score of the experimental group (15.6), the increase was notably significant; however, there was no significant alteration in the mean pre-test (14.6) and post-test (14.9) knowledge scores within the control group. The variance between the average pre-test and post-test knowledge scores of the experimental group exhibited statistical significance with a p-value below 0.001. Research hypothesis H1 was accepted at p< 0.001 level of significance and null hypothesis H0 was rejected at p<0.05 level of significance
Keywords: Experimental research; factors; hypothesis; knowledge score; socio political issues